Performance And Economic Viability Of Broiler Chickens Fed With Probiotic And Organic Acids In An Attempt To Replace Growth-Promoting Antibiotics - Araujo,RGAC (2019)
ABSTRACT The aim of this study was to evaluate diets supplemented with probiotic (Bacillus amyloliquefaciens) and organic acids (lactic, acetic and butyric acid) in attempt to replace the antibiotics and anticoccidial (avilamycin + sodium monensin) growth promoters on performance and economic viability of broilers challenged by Eimeria acervulina, E. maxima and E. tenella. A total of 900 male Cobb® chickens, with a mean weight of 39.90g, were distributed in a completely randomized design in a 2 × 2 + 1 factorial arrangement: supplementation or not of probiotic and organic acids and a treatment with inclusion of antibiotics, comprising five treatments with six replicates. For the studied performance variables, there was no effect of the isolated additives and no interaction between them (p>0.05). Only the antibiotics promoted better results for weight gain (WG), feed intake (FI) and feed conversion rate (FCR). Therefore, the use of organic acids and probiotic, isolated or associated, provided lower performance to those receiving antibiotics, not improving the performance of chickens under the imposed challenge conditions. The highest revenues were generated with the use of antibiotics, providing greater profits.